2018
DOI: 10.1021/acs.jctc.7b01269
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Automatized Density-Functional Tight-Binding Parametrizations: Application to Group IV Elements

Abstract: Density-functional tight-binding methods stand out as a very good compromise between accuracy and computational efficiency. These methods rely on parameter sets that have to be determined and tabulated for every pair of chemical elements. We describe an efficient, and to a large extent automatic, procedure to build such parameter sets. This procedure includes the generation of unbiased training sets and subsequent optimization of the parameters using a pattern search method. As target for the optimization we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…25 For this step, we used home-made high-quality Slater-Koster parameters, specifically fitted to obtain energies and forces with quasi-DFT precision. 35 The number of calculations also forced us to neglect spin-orbit coupling at this stage, although we verified a posteriori that this is acceptable (see below).…”
mentioning
confidence: 76%
“…25 For this step, we used home-made high-quality Slater-Koster parameters, specifically fitted to obtain energies and forces with quasi-DFT precision. 35 The number of calculations also forced us to neglect spin-orbit coupling at this stage, although we verified a posteriori that this is acceptable (see below).…”
mentioning
confidence: 76%
“…A number of recent DFTB parameterizations have, in addition to fitting the repulsive potential, empirically adjusted parameters that define the electronic Hamiltonian during the fitting process. [53][54][55][56][57] Adjusted parameters include those that define the constraining potential and electron density cutoffs in the standard approach utilized to construct the DFTB electronic Hamiltonian from QC solutions for isolated atoms. 53,55,56 Empirical fits have also adjusted the atomic orbital energies, and the Hubbard parameters that specify electron-electron repulsion.…”
Section: Related Workmentioning
confidence: 99%
“…Huran et al. employed a pattern‐search algorithm for parameterizing the electronic and repulsive potential at the same time for Group IV elements …”
Section: Dftb Parameterizationmentioning
confidence: 99%
“…The confining radii in the electronic parameters were conventionally heuristically chosen but in the recent years they have been usually optimized to electronic band structures prior to the optimization of the repulsive potentials. However, recent developments have shown that it may be necessary to optimize both electronic and repulsive parts simultaneously to have better performance and transferability due to error compensation ,,,. Thus, we tried to optimize the confining potentials to reproduce the bonding angles between the Li cation and the selected ligands including the standard H 2 O, NH 3 molecules, and common used organic electrolyte molecules.…”
Section: Illustrative Applicationsmentioning
confidence: 99%